Decision making model for evaluation of TPACK knowledge constructs as critical success factors for language learning classes - Huma Batool; Salman Al-Otaibi; Majid Khan (Heliyon)
The aim of this article is to investigate the key success factors of technology, pedagogy and content knowledge (TPACK) in language learning classrooms. We used multi criteria decision making (MCDM) technique namely analytical hierarchy process (AHP) along with group decision making (GDM) in order to classify and rank the critical factors involved in TPACK. The classification and ranking of each factor of TPACK systematized and regularized the importance of technology-driven teaching and learning in language classrooms. Our study provides a new decision making model for TPACK constructs, offering valuable understanding for improving technology driven instructional strategies in language learning.